2007
DOI: 10.1152/ajpheart.00678.2006
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelium-derived factors and arterial stiffness in strength- and endurance-trained men

Abstract: Otsuki T, Maeda S, Iemitsu M, Saito Y, Tanimura Y, Ajisaka R, Miyauchi T. Vascular endothelium-derived factors and arterial stiffness in strength-and endurance-trained men. Am J Physiol Heart Circ Physiol 292: H786 -H791, 2007. First published September 22, 2006; doi:10.1152/ajpheart.00678.2006.-Arterial stiffness is higher in strength-trained humans and lower in endurance-trained humans. However, the mechanisms underlying these different adaptations are unclear. Vascular endothelium-derived factors, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
4
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(101 citation statements)
references
References 37 publications
6
84
4
2
Order By: Relevance
“…We and other groups have reported that arterial compliance at rest is greater in physically active or ET than SC humans (4,12,15,29,30,32,45,47). Intervention studies have also demonstrated that endurance exercise training increases arterial compliance (6,40,46).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…We and other groups have reported that arterial compliance at rest is greater in physically active or ET than SC humans (4,12,15,29,30,32,45,47). Intervention studies have also demonstrated that endurance exercise training increases arterial compliance (6,40,46).…”
Section: Discussionmentioning
confidence: 85%
“…Although there are no differences in blood pressure at rest between the ET and SC humans, blood pressure is higher at maximal exercise load in the ET subjects, indicating the increases in blood pressure from rest to maximal exercise are greater in the ET than SC humans (33,38). Additionally, increased arterial compliance at rest in ET humans (4,6,12,15,29,30,32,40,(45)(46)(47), compared with SC humans, may increase the C reserve during exercise. Taken together, it is possible that the reductions of C from rest to exercise are more remarkable in ET humans compared with SC humans.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Aerobic training improves vascular load (i.e., arterial stiffness 4,14,15) and vascular conductance 14,16) ) and blunts sympathetic vasoconstriction during exercise (functional sympatholysis) 17) . It has also been reported that endurance-trained athletes 18,19) and physically active men with autism spectrum disorder 20) have lower arterial stiffness. These vascular changes after the training period possibly lower SBP during aerobic exercise.…”
Section: Effects Of Habitual Exercise On Blood Pressure During Exercisementioning
confidence: 93%
“…We have reported that arterial stiffness is higher in strength-trained individuals 18) . Arterial stiffening in strength-trained individuals may be associated with higher levels of plasma endothelin-1, a vasoconstrictor peptide 19) . On the other hand, aerobic training, which does not require intense muscle contractions, decreases vascular load [14][15][16] and increases functional sympatholysis 17) .…”
Section: Effects Of Habitual Exercise On Blood Pressure During Exercisementioning
confidence: 99%